Complementary Therapy in Patients with Multiple Sclerosis - Payamani F; Nazari AA; Noktehdan H; Ghadiriyan F; Karami K (Iran University of Medical Sciences, 2012)
Background & Aim : Given the high cost of medical treatment to control the symptoms of Multiple Sclerosis (MS) and the resulted numerous complications, the use of complementary therapy has been increased by these patients. This study aims to determine the status of complimentary therapy in patients with MS who refer to MS Association in Tehran in 2008.   Material & Methods : It was a descriptive cross- sectional study. Two hundred patients with MS were recruited by convenience sampling. Data was collected by a researcher made questionnaire using face-to-face interviews and analyzed by descriptive and inferential (Chi-square and ANOVA) statistics using SPSS-PC (v. 11.5).   Results : More than half of sample (60%) has used complimentary therapy. All of them had used non-pharmacological treatment as a supplement and not as a replacement to therapy. The most frequently used methods were exercise, meditation, nutrition therapy, herbal medicines, energy therapy, acupuncture and acupressure respectively. The results also showed that the majority of participants (44/5%) have used one non-pharmacological method and just 11.5% have used two methods or more . The findings showed that there is o significant relationship between using complimentary therapy and demographic characteristics of patients except for educational level (P=0/04).   Conclusion: Regarding the widespread use of complementary therapy by patients with MS, these patients are exposed to potential risks and side effects of the treatments. So it is recommended that patients be provided with necessary training. Doing more research on the methods of complimentary therapy and assessment of the reasons for tendency to this type of treatment is also recommended.  Received: 9 Jun 2012   Accepted: 16 Aug 2012